2010
DOI: 10.1080/08838151.2010.519810
|View full text |Cite
|
Sign up to set email alerts
|

A Cognitive Processing Model of Information Source Use and Stereotyping: African-American Stereotypes in South Korea

Abstract: This study proposes a cognitive processing model to explain that stereotypes are the result of a two-way interaction between receiver evaluation of the valence of accessed information from the media, and receiver evaluation of the realism and believability of the information. This model is applied to analyze American media use and stereotyping of African-Americans among 378 high school students in South Korea. Findings partially support the proposed model: positive media portrayals perceived to be real and bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…This indicates that regardless of the training procedure used, increased tolerance scores were achieved in less than 1 hr. Such outcomes are consistent with the goals outlined for educating children about the diversity of others with regard to religion (e.g., American Academy of Religion, Religion in the Schools Task Force, 2010; Rosenblith & Bailey, 2008;Tan, Dalisay, Zhang, Han, & Merchant, 2010). In the current study, however, we did not determine whether increases in reported tolerance of others would generalize to real-world social interactions with people of diverse religious backgrounds.…”
Section: Discussionsupporting
confidence: 76%
“…This indicates that regardless of the training procedure used, increased tolerance scores were achieved in less than 1 hr. Such outcomes are consistent with the goals outlined for educating children about the diversity of others with regard to religion (e.g., American Academy of Religion, Religion in the Schools Task Force, 2010; Rosenblith & Bailey, 2008;Tan, Dalisay, Zhang, Han, & Merchant, 2010). In the current study, however, we did not determine whether increases in reported tolerance of others would generalize to real-world social interactions with people of diverse religious backgrounds.…”
Section: Discussionsupporting
confidence: 76%
“…Subsequently, the audience may gain negative feelings about this group. In conclusion, both theories emphasize the social influence of media images and were confirmed by previous research showing that media influence how Others perceive themselves and how they are perceived by others (Mastro et al, 2008;Sakuma and Hiyoshi, 2016;Tan et al, 2010;Tukachinsky et al, 2017).…”
supporting
confidence: 77%
“…EU citizens' portrayal in the media is important, as it can reduce prejudice, especially if interpersonal contacts are rare (cf. Schiappa et al 2005;Shim et al 2012), but it can also foster negative stereotypes (Tan et al 2010). Certain circumstances, such as political or economic crises, provide an opportunity to highlight and strengthen bonds and similarities between the citizens of the EU member states, but they can also trigger a resurgence of national sentiments by emphasizing the opposite.…”
Section: Introductionmentioning
confidence: 99%